Juggling Family Care Responsibilities and Personal Aspirations: The ‘Invisible Care’ Provided by Young Adults - Bosoni, Maria Letizia; Carradore, Marco (Italian Sociological Review, 2025)
This paper underscores the crucial role of personal networks and social capital in mitigating the stress young adults endure as a consequence of caregiving responsibilities. The study explores the experiences of young adult carers (YACs) aged 18–37 years who provide informal and ongoing care to family members with chronic illness, disability, or age-related conditions. Drawing on qualitative data from ten caregiver-supporter dyads in Italy, the research investigates how caregiving impacts personal development, relational dynamics and future planning during early adulthood. Using an innovative methodology combining personal network interviews and dyadic sessions, the study captures the structure and function of formal and informal support networks, as well as the subjective experiences of carers. The findings revealed two caregiving configurations: “supportive dyads,” where the supporter primarily provides emotional and organizational help to the carer; and “collaborative dyads,” where both members are actively involved in direct caregiving. In both cases, the carer, who is central to the support network, acts as a bridge between family and external connections. Although supportive relationships, particularly with partners, play a protective role in buffering caregiver strain, the burden of care significantly constrains carers’ autonomy, career progression, and relational well-being. However, the findings also point to the limitations of these networks when broader systemic support is lacking. The paper calls for enhanced policy recognition and targeted interventions to support young adult carers, whose roles still largely go unrecognized in public discourse and institutional practice.